The impact of the position of the head on the functioning of the human body: a systematic review - Elżbieta Szczygieł; Natalia Fudacz; Joanna Golec; Edward Golec (International Journal of Occupational Medicine and Environmental Health, 2020)
The head is an important element of the biokinetic chain. Under physiological conditions, it should extend along the midline of the body. Due to its location and the fact that it constitutes approx. 6% of the total body weight, many authors believe it has a significant impact on its functioning. The aim of this study was to conduct a systematic literature search and to synthesize the evidence of the impact of the head posture on the functioning of the human body. A systematic review was conducted within 3 databases: PubMed, Medline OVID, and EBSCO, using the following terms: “forward head,” “posture,” “position,” and “neck.” For the analysis, scientific articles published after 2013 were selected. A total of 16 studies matched the inclusion criteria of this systematic review. Their results have proven that the position of the head has a significant effect on the human body. Research findings show that abnormal head position changes affect muscle activity, proprioception, the pattern of breathing and neck pain. This is the first systematic review of the relationship between the head posture, and the functioning of the human body. The results of this study seem to be promising if used in therapeutic practice. Int J Occup Med Environ Health. 2020;33(5):559–68